2020
DOI: 10.33393/abtpn.2020.2184
|View full text |Cite
|
Sign up to set email alerts
|

Time to reimbursement and negotiation condition in Italy for drugs approved by the European Medicines Agency during the period 2014-2019

Abstract: Introduction: The main purpose of this study was comparing median time (TTR, time to reimbursement) between the first Agenzia Italiana del Farmaco (AIFA) pricing and reimbursement (P&R) dossier’s evaluation and patient access in Italy and to observe the key P&R negotiation results for all new active substances approved by the European Medicines Agency (EMA)’s Committee for Medicinal Products for Human Use between January 2014 and December 2019. We analysed the different factors influencing TTR. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…On the other hand, there is uncertainty about the association of some explanatory variables with negotiation outputs. Indeed, as in our study, Lidonnici et al (13) confirmed the significant impact of the therapeutic area and the significant negative impact of the registry presence on TTM, while Prada et al (14) recognized drug innovativeness as the only significant element in the negotiation.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…On the other hand, there is uncertainty about the association of some explanatory variables with negotiation outputs. Indeed, as in our study, Lidonnici et al (13) confirmed the significant impact of the therapeutic area and the significant negative impact of the registry presence on TTM, while Prada et al (14) recognized drug innovativeness as the only significant element in the negotiation.…”
Section: Discussionsupporting
confidence: 84%
“…In a later publication based on the same data, Raimondo et al (15), found that TTM increased to 287 days in the 2018-2020 three-year period. Similarly, Prada et al (12,14), only including reimbursed new active substances approved from 2014 to 2019, estimated an average of 228 days and, when focusing on the reimbursed oncological drugs, estimated a time to reimbursement of 248 days.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations